Investigation of thermal dynamics for different leading configuration in hybrid laser-MIG welding. (February 2021) - Chen, Xuyang; Yu, Gang; He, Xiuli; Li, Shaoxia
Highlights: An improved model was proposed to simulate the hybrid laser-MIG welding. The thermal dynamics was strongly affected by the leading configuration. The molten pool was more homogeneous for laser-leading configuration. The concentration was not fully mixed for arc-leading configuration. Abstract: For hybrid laser-MIG welding of aluminum alloy, the weld bead quality is decided by the thermal dynamics in the molten pool. In order to analyze the influence of leading configuration on thermal behavior and mass transfer, a three-dimensional numerical model is established. In the model, a combined model is utilized to simulate the multiple reflections and Fresnel absorption of laser beam. The laser-arc interaction is considered and the plasma is shrinked for arc-leading configuration. Surface tension, electromagnetic force, buoyancy are considered to investigate the fluid flow pattern, and droplet impact and arc pressure are taken into account to track the free surface. For different configurations, the temperature and velocity field, together with concentration distribution of magnesium and zinc are compared and analyzed. The results show that transport phenomena of the molten pool is strongly affected by the configuration. For arc-leading (AL) configuration, it is easier to get a larger penetration. Meanwhile, the concentration distribution of magnesium and zinc is more homogeneous for laser-leading (LL) configuration. Furthermore, the developed model can provide theoretical basis for processing experiments.